EVALUATION OF DIFFERENT MULCH MATERIALS AND SHELTER, IN THE ESTABLISHMENT OF PLANTS OF Pinus taeda L., BY DIRECT SOWING - Marcio Ricardo Serpa; Vilmar Luciano Mattei (Ciência Florestal, 2009)
This work has had as its objectives to evaluate different covering materials and physical protector's use in the forest population of Pinus taeda L. in direct sowing in the field. Three materials were used: vermiculit, dried and pricked pine needles, peel of rice and reference without covering, with and without physical protector (plastic cup of 300 ml, without botton), with five replications. The sowing was accomplished in the first half of May of 1997, being used three seeds per point. The evaluations done were: emergency at the 60 and 90 days, survival at the 120, 180 and 210 days and population density at the 210 days after sowing. The variance and averages analysis (Duncan 5%), has allowed to conclude that: the vermiculit and pine needles affected beneficially the number of plants emerged in the first 60 days, that is the most critical phase for the future of the forest population of Pinus taeda; the physical protector, provides the formation of a microenvironment, that guarantees larger percentage in the emergence, survival and initial density of plants of Pinus taeda; the direct sowing demonstrated to be a viable technique.